Effectiveness of Video Assessted Educational Programme Towards Breast Self Examination Among Rural Women - Shete, Sushama; Shinde, Mahadeo B; Katti, Rohini (International Journal of Psychosocial Rehabilitation, 2020)
Appropriate protective strategies direction on both primary and secondary preventive mechanisms is needed to decrease the incidence of breast cancer. Objectives: To assess the women’s knowledge on breast self examination before and after intervention. To find out an association with women’s knowledge on breast self examination the demographic variables. Material & Methods.Evaluative research approach was used. Research design- Quasi experimental (one group pre & post test design). Study was done on 49 subjects from community Gondi, Karad. Using Non Probability Convenient sampling technique The data collected using pre tested questionnaire. Frequency distribution analysis was performed. Result: Among 49 Majority of the subjects 16 (32.6 %) age 41-50 year ,Majority women’s from Hindu family and women’s from secondary school education 26 (53.6%). 100% women’s from rural community, majority samples is married ie 41(83.6%) About occupation out of 49 women’s 47 (95.9) % were housewife 27 (55.1%) from joint family. Out of 49 women’s history of no breast cancer None 46(93.8%). And Habit of tobacco 40(81.6%) Mean, standard deviation of score obtained before and after administration of the video assisted educational programme on knowledge of women’s on breast self examination Conclusion: Video assisted educational program was effectivestrategy to improve knowledge of women’s on breast self examination